Edaphic fauna in wooded systems of conilon coffee in coastal tableland soil - Rabelo Teixeira, Alex Fabian; Maurício da Silva, Victor; de Sá Mendonça, Eduardo (Coffee Science - ISSN 1984-3909, 2014)
The Espirito Santo is the biggest Brazilian producer of coffee conilon, highlighting the predominance of monocultures in the northern region. Some farmers insert tree species in plantations, modifying the soil and climate conditions of the agroecosystems. However, studies on the effect of this practice in relation to soil fauna are still incipient. The objective of this work was study the effect of forestation in conilon coffee plantations on meso-and macrofauna of the soil in the northern of Espirito Santo state. In the rainy and dry seasons, the meso-and macrofauna was sampled using pitfall traps installed in three coffee plants agroecosystems: monoculture, intercropped with Australian cedar (Toona ciliata M. Romer), and intercropped with teak (Tectona grandis L. f.). Subsequently the organisms of fauna were identified in major taxonomic groups. We collected a total of 10,451 invertebrates on the soil surface, belonging to 20 taxonomic groups, mostly during the rainy season. Regardless of the period and system, Collembola and Formicidae were the predominant groups on the soil surface. The richness of taxonomic groups was higher during the dry season in all agroecosystems. In the rainy season, the Shannon diversity index (H’) and Uniformity index (U) were higher (p <0.10) in consortium with cedar compared to other systems, with values of 0.45 and 0.68, respectively. The forestation of coffee plantation with Australian cedar provides greater availability of resources (feeding and habitat, for example) to soil fauna, being less vulnerable to seasonal climate changes.